Role of Armed Police Force, Nepal in Promoting Good Governance through Border Security - Aryal, Raju (Journal of APF Command and Staff College, 2022)
The Armed Police Force, Nepal was established for the protection of the life, property, and liberty of the people by maintaining peace and order in Nepal. Border security is a broad agenda of the national security and Armed Police Force, Nepal is a primary national security element on international border security of Nepal. The objective of the paper is to link the good governance and border management. The descriptive method is applied to draw the conclusion in this paper. The findings show that the Armed Police Force, Nepal has a major contribution in controlling trans-border crimes in coordination with other stakeholders and counterparts which directly contribute to promoting good governance in Nepal. Effective border management comply the most principles of the good governance: preparedness, participation, transparency, accountability and protection of human rights. Furthermore, it is found that border security has a significant positive relationship with good governance. Maintaining national integrity, safeguarding the independence and sovereignty of the nation, maintaining justice, and ethics, being free from corruption, and maintaining the rule of law are the primary independent indicators of promoting good governance through border security.